(untitled) - FAO (Rome, 1997)
The information contained in this publication, in addition to being useful as specialized reference material, may also be a source of inspiration for policymakers and decisionmakers in general, and governmental legal advisers and negotiators in particular, as they deal with the uniquely complex legal implications of developing, using and protecting water resources shared across international borders.
Keywords: environmental law, international,natural resources